First Report of Dieback of Citrus Trees Caused by Nattrassia mangiferae in South of Iran - Keshavarz, Kavoos; Mirinejad, Shahab; Keveshk, Nematallah Mortazavi (Asian Journal of Biological and Life Sciences)
Wilting, dieback, decline and death of citrus trees have spread out extensively in tropical areas of South of Iran. The aim of this study was identifying the causative agent, dispersion and prevalence of this disease in different regions. About 170 samples suspected of having this disease from different areas were transferred to the laboratory and finally 18 fungal isolates were extracted. Fungal isolates grew very well in 30-35oC and PDA culture. Pycnidia were almost spherical in the medium and they varied from dark brown to black. Arthroconidium stage of pathogenic fungi was identified and arthroconidia were mostly cylindrical under microscope and flat at both ends. Their length was twice their width and without walls, however, they sometimes had walls as well. According to morphologic features and some physiologic aspects along with pathogenicity on detached branches of citrus trees as well as citrus trees in garden conditions and matching them with other sources including Sutton and Dyko article in 1989, the mentioned pathogen was identified to be Nattrassia mangiferae. Results showed that the highest symptoms were observed in Poshtkooh, Marin and Basht areas, in such a way that in Posthkooh region about 75% of lime trees showed the symptoms of this disease. This is the first report of Nattrassia mangiferae as a causal agent of dieback of citrus trees in South of Iran.
Keywords: Decline; Fungi; Wilting Citrus